Drivers of Entrepreneurial Intent: The Roles of Motivation, Knowledge, Income Expectations, and Self-Efficacy - Nasution, Ade Iskandar; Halim, Asep Abdul; Nur'aeni, Nur'aeni (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
This study analyzes the influence of entrepreneurial motivation, entrepreneurial knowledge, income expectations, and self-efficacy on entrepreneurial interest. A quantitative method was employed, with a questionnaire distributed to 141 respondents, and the data were analyzed using measurement models and path analysis. The results indicate that entrepreneurial motivation (coefficient 0.051; t-statistic 0.654) and entrepreneurial knowledge (coefficient 0.097; t-statistic 0.417) are not significant predictors of entrepreneurial interest. In contrast, income expectations (coefficient 0.268; t-statistic 0.009) and self-efficacy (coefficient 0.197; t-statistic 0.020) have significant effects. These findings underscore the importance of economic and psychological factors in fostering entrepreneurial interest. Effective training and education programs are necessary to enhance understanding of financial benefits and to build confidence and entrepreneurial skills.